Exit, voice or loyalty? VET stakeholders' response to large scale skilled emigration from Poland - Kaja Reegård; Horacy Dębowski (International Journal for Research in Vocational Education and Training (IJRVET), 2020)
Context: The topic of this paper is how mass emigration of skilled workers affects national policies, and employers' willingness to invest in Vocational Education and Training (VET) in Poland. In the wake of EU enlargement in 2004, Poland became one of the biggest sending countries for skilled labour to Western European countries. These massive outflows of skilled labour, not compensated by adequate inflows of equally skilled workers, have led to serious skills shortages, especially in the construction sector. The paper investigates whether emigration and immigration constitute a driving force for institutional change of the Polish VET system, by analysing policy development and the attitudes of VET stakeholders towards contributing to VET. Approach: The paper focuses on the emigration of skilled construction workers in Poland. Drawing on Hirschman's (1970) framework, when faced with massive skills deficits construction companies are confronted with different options: i) withdraw from the VET system and find other training and recruitment options (exit), ii) attempt to improve conditions by turning to policy makers (voice), and/or iii) remain loyal to the VET system. The analysis is based on an interview study of decision makers responsible for VET policies, employers, chamber of Craft and trade unions, principals of vocational schools, teachers and representatives of regional examination boards. Findings: After years of inattention, VET has been regaining a strong position in national policies. We find that construction companies are mostly more willing now, compared to 5 years ago, to take on learners for practical training and to contribute to improving school equipment. The study showed that one of the most significant obstacles to employers investing in the training of VET learners is the fear of losing a young skilled employee through emigration. Yet, dependent on skilled labour, employers of big construction companies saw no other option than to continue investing in training young learners. However, smaller companies seeking the short-term benefits of employing low-cost labour are less interested in investing in VET. Conclusion: Despite a range of recent policy actions and legislative efforts, several major challenges in the Polish VET system remain unresolved. Continued effort to institutionalise and enhance dialogue between the education system and the labour market appears as the most pressing need. It is currently too early to determine the degree of "institutional stickiness" of the activities observed on the policy level and among employers regarding their increased interest in VET as a response to mass skilled emigration.
Keywords: 330; Vocational Education and Training; VET; Skilled Migration; Labour Shortage; Labour Mobility; Education-Industry Relationship; Educational Policy